Four stages of hepatic hematopoiesis in human embryos and fetuses. (19th March 2018) - Fanni, D.; Angotzi, F.; Lai, F.; Gerosa, C.; Senes, G.; Fanos, V.; Faa, G.
Abstract: The liver is a major hematopoietic organ during embryonic and fetal development in humans. Its hematopoietic activity starts during the first weeks of gestation and continues until birth. During this period the liver is colonized by undifferentiated hematopoietic stem cells (HSCs) that gradually differentiate and once mature, enter the circulatory system through the hepatic sinusoids, this process is called hepatic hematopoiesis. The morphology of hepatic hematopoiesis, has been studied in humans through the years, and led to a characterization of all the cell types that make up these phenomena. Studies on murine models also helped to describe the extent of hepatic hematopoiesis at different gestational ages. Using this knowledge, we attempted to describe how hepatic hematopoiesis morphologically evolves as gestation progresses, in human embryos and fetuses. Thus, we observed a total of 32 tissue specimens obtained from the livers of embryos and fetuses at different gestational ages. Basing our observations on the four stages of liver hematopoiesis identified by Sasaki and Sonoda in mice, we also described four consecutive stages of liver hematopoiesis in humans, which resulted to be highly similar to those described in murine models.